2021
DOI: 10.3389/fcell.2021.767668
|View full text |Cite
|
Sign up to set email alerts
|

Role of Main RNA Methylation in Hepatocellular Carcinoma: N6-Methyladenosine, 5-Methylcytosine, and N1-Methyladenosine

Abstract: RNA methylation is considered a significant epigenetic modification, a process that does not alter gene sequence but may play a necessary role in multiple biological processes, such as gene expression, genome editing, and cellular differentiation. With advances in RNA detection, various forms of RNA methylation can be found, including N6-methyladenosine (m6A), N1-methyladenosine (m1A), and 5-methylcytosine (m5C). Emerging reports confirm that dysregulation of RNA methylation gives rise to a variety of human di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 95 publications
0
25
0
Order By: Relevance
“…Based on the abovementioned analysis and previous articles, genes had an important and complex role in HCC. 19 The genes whose fold changes were >1.5 and with FDR adjusted p-value < 0.05 were determined as differential genes (DEGs). 20 Figure 5A shows the association between DEGs, except for YTHDF3 and ALYREF , and most DEGs were positively correlated with each other, thereby suggesting the synergistic role of genes in the development of HCC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the abovementioned analysis and previous articles, genes had an important and complex role in HCC. 19 The genes whose fold changes were >1.5 and with FDR adjusted p-value < 0.05 were determined as differential genes (DEGs). 20 Figure 5A shows the association between DEGs, except for YTHDF3 and ALYREF , and most DEGs were positively correlated with each other, thereby suggesting the synergistic role of genes in the development of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the role of RNA methylation genes in tumors, an RNA methylation gene-based prognostic model was established based on related studies. 19 Results showed that the model was a more accurate predictor of patient prognosis and that low-risk patients had a higher degree of immune infiltration and expression of immunosuppressive genes than low-risk patients. In mRNA, m5C modification can have a significant effect on metabolism.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…RNA methylation is considered an important process in epigenetic regulation, which occurs in mRNA and in ncRNA ( Xu et al, 2021 ). Various forms of RNA methylation exist depending on the site of methylation, including N1-methyladenosine (m1A), 5-methylcytosine (m5C), N6-methyladenosine (m6A), 7-methylguanosine (m7G), and 2-O-dimethyladenosine (m6Am) ( Xie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%